Comparison of jet injection technique with conventional injection technique in patients undergoing endodontic therapy - Mahaboob Shahul Hameed; Senthil Kumar; C Charanya; M Muthalagu; M Anitha (Wolters Kluwer Medknow Publications, 2021)
Background: In order to reduce the fear and anxiety of injection during root canal procedures, Madajet injection technique was substituted for the first time among the adult patients to obtain its efficacy and to overcome the painful procedure during the conventional syringe technique. Aim: The aim of this study is to compare the clinical efficacy and level of patient acceptance of jet injections with conventional syringe technique in patients with symptomatic pulpitis. Methodology: Seventy patients were randomly divided into needleless pressure injection technique using Madajet XL and conventional syringe technique. The onset of anesthesia was evaluated using the electric pulp tester, and the pain was assessed using the Visual Analog Scale scoring criteria. Statistical Analysis: The obtained data were tabulated and subjected to the statistical analysis using the Chi-square test. Results: Needleless pressure injection technique (Madajet XL) proves to be effective in patients with symptomatic irreversible pulpitis during endodontic procedure. Conclusion: It can be concluded that the needle-less pressure injection technique (Madajet XL) promises to be a viable mode of pain control during endodontic procedures as it converts the solution to a tiny droplet which is then carried by the myelin sheath.